The growth of three varieties of black pepper (Piper nigrum) under different light intensities related to indigenous hormones role - Issukindarsyah Issukindarsyah; Endang Sulistyaningsih; Didik Indradewa; Eka Tarwaca Susila Putra (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Issukindarsyah, Sulistyaningsih E, Indradewa D, Putra ETS. 2020. The growth of three varieties of black pepper (Piper nigrum) under different light intensities related to indigenous hormones role. Biodiversitas 21: 1778-1785. Low light intensity causes the alteration of plant biochemical and morphological as the mechanism of adaptation. The experiment used split-plot design with three replications. The main plots were three light intensity levels, i.e. 100%, 75%, and 50% radiation; while subplots were three varieties namely Nyelungkup, Petaling 1 and Petaling 2. This research was conducted to figure out the effect of shadings on hormones and the growth of three varieties of black pepper (Piper nigrum L.). The results showed that in initial vegetative growth, varieties of Nyelungkup and Petaling 1 had higher growth of both ortotroph and plagiotroph branches, leaf number, leaf area, length of root, root surface area, plant dry weight, nett assimilation rate, and plant growth rate than the variety of Petaling 2. The light intensity of 50% and 75% increased the auxin and gibberellin contents of the leaf but they did not affect the zeatin. The maximum gibberellin and auxin contents of leaf were recorded at 75% light intensity. The 50% and 75% light intensity raised the length, diameter, and internode of ortotroph branch; number, length, and internode of plagiotroph branch; leaf number; leaf area; leaf area ratio; length of root; root surface area; plant growth rate and plant dry weight related to indigenous hormones role.